Fluorimetric naphthalimide-based polymer logic beads responsive to acidity and oxidisability. Issue 48 (20th November 2019) - Refalo, Matthew Vella; Farrugia, Nicole V.; Johnson, Alex D.; Klejna, Sylwia; Szaciłowski, Konrad; Magri, David C.
Abstract : Naphthalimide tagged polymer beads demonstrate two-input H +, Fe 3+ -driven PASS 0, PASS 1, TRANSFER(H + ) and AND logic functions by a fluorescence output. Abstract : Molecular logic gates were synthesised and surface immobilised onto TentaGel® MB-NH2 (amino terminal functionalised polyethylene glycol ligands on polystyrene beads). Four naphthalimide-based tagged polymer solid beads are demonstrated expressing two-input H +, Fe 3+ -driven PASS 1, TRANSFER (H + ) and AND Boolean logic functions. The photophysical properties of the model molecular compounds were studied by UV-visible absorption and fluorescence spectroscopy in 1 : 1 (v/v) methanol/water. TD-DFT calculations of the molecular Pourbaix sensors give insight into the mechanistic details of fluorescence modulation controlled by internal charge transfer (ICT) and photoinduced electron transfer (PET). Both colour and fluorescence emission can be used to distinguish the heterogeneous polymer beads. Stimulated by H + and/or an oxidant input(s) we demonstrate blue emitting two-input H +, Fe 3+ -driven PASS 1, and green emitting H +, Fe 3+ -driven two-input TRANSFER (H + ) and H +, Fe 3+ -driven two-input AND tagged solid beads.